Profil Kompetensi Kepribadian pada Guru Bimbingan dan Konseling Fresh Graduate Untirta - Ramdhini, Puji; Khairun, Deasy Yunika; Nurmala, Meilla Dwi (Program Studi Bimbingan dan Konseling, 2024)
This research aimed to determine the personality competence of guidance and counseling teachers, especially fresh graduate teachers. The research employed a quantitative descriptive research method and used total sampling techniques to gather 32 respondents from the fresh graduate guidance and counseling teachers at Universitas Sultan Ageng Tirtayasa as the research sample. Data was collected using a Likert scale questionnaire. The research findings indicated that the personality competence of the fresh graduate guidance and counseling teachers from Untirta fell into the high category, at 87,5%. Meanwhile, in the moderate category, it was at 12.5%, and in the low category, it was 0%. Consequently, it can be concluded that the majority of the fresh graduate guidance and counseling teachers from Untirta have a high level of personality competence according to the provisions of the National Education Minister Regulation No. 27 of 2008 concerning Academic Qualification Standards and Counselor Competence. Keywords: Fresh graduates; guidance and counseling teacher; personality competency